2013
DOI: 10.7232/jkiie.2013.39.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Optimization : Current Status and Vitalization Suggestions

Abstract: Healthcare optimization is mandatory to strengthen the competitiveness of domestic healthcare industry. Healthcare optimization aims to increase service quality, patient safety, and system efficiency. This paper reviews various healthcare optimization cases of developed countries, synopsizes the current status of domestic healthcare industry, points out several reasons why healthcare optimization is not active in Korea, and suggests some vitalization ways. †

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
1
0
1
Order By: Relevance
“…Lee et al reported that the quality of Korean primary medical institutions (0.3) was much poorer than that of the UK (1.9) or Canada (1.2) [ 30 ]. In addition, the results reflect that tertiary hospitals are equipped better, because they can provide a variety of medical services compared with community hospitals and clinics in Korean healthcare system [ 31 ]. To prevent relapse in patients with first-episode schizophrenia, environmental and institutional reorganization will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al reported that the quality of Korean primary medical institutions (0.3) was much poorer than that of the UK (1.9) or Canada (1.2) [ 30 ]. In addition, the results reflect that tertiary hospitals are equipped better, because they can provide a variety of medical services compared with community hospitals and clinics in Korean healthcare system [ 31 ]. To prevent relapse in patients with first-episode schizophrenia, environmental and institutional reorganization will be required.…”
Section: Discussionmentioning
confidence: 99%
“…이러한 개개 인의 특성을 반영할 수 없는 수리적 모델의 단점을 극복하기 위하여 시뮬레이션 모델이 사용되었다. 시뮬레이션 모델은 전 염병뿐만 아니라 의료서비스 전반에 걸쳐 많이 쓰이는 방법론 이다 (Brailsford, 2007;Koo et al, 2012;Kang et al, 2013 (Lee et al, 2010, Chao et al, 2010, Chen et al, 2010. 국외의 경우, 잘 만들어진 지역 단위의 시뮬레이션 모델들이 존재한다 (Smith et al, 1995;Del Valle et al, 2006;Chao et al, 2010;Stein et al, 2013 …”
Section: 서 론unclassified